Are your international salespeople culturally intelligent? The influence of cultural intelligence on adaptive selling behavior with B2B customers. Issue 4 (3rd August 2021) - Kimber, David; Guesalaga, Rodrigo; Dickmann, Michael
Abstract : Purpose: This study aims to investigate cultural intelligence (CQ) as an antecedent of adaptive selling behavior (ASB) and cultural distance and intrinsic motivation as moderators in this relationship. Design/methodology/approach: This research builds on a survey to 310 US-based international sales executives (ISE) and multiple regression analysis to test the hypotheses. Findings: The results show that CQ has a significant positive relationship with ASB, both as an aggregate construct and through its metacognitive, motivational and behavioral facets. Also, intrinsic motivation moderates such relationship, whereas cultural distance does not. Research limitations/implications: The study includes only a sample of US-based international salespeople in the B2B context, which limits the generalizability of the findings to salespeople from other countries or other contexts. Practical implications: The findings of this research suggest that supplier companies involved in international selling should consider the cultural intelligence of their salespeople for selection, training and coaching. Originality/value: This study makes an important contribution to the literature on both ASB and CQ by expanding the knowledge on how to manage international salespeople effectively, considering the conditions under which CQ effects are expected and how these vary in this context.